The application of voksel model at the designing of electronic cloud - Сидоренко, Анна Юрьевна; Потапенко, Алена Игоревна (Bulletin of National Technical University "KhPI". Series: System Analysis, Control and Information Technologies, 2013)
The structure of 3D model of electronic cloud of atom of hydrogen is shown in a cut and in a valuable kind by means of voxel model. Wave functions are built.